2022
DOI: 10.1177/09567976221082942
|View full text |Cite
|
Sign up to set email alerts
|

Too Reluctant to Reach Out: Receiving Social Support Is More Positive Than Expressers Expect

Abstract: Receiving social support is critical for well-being, but concerns about a recipient’s reaction could make people reluctant to express such support. Our studies indicate that people’s expectations about how their support will be received predict their likelihood of expressing it (Study 1, N = 100 online adults), but these expectations are systematically miscalibrated. Participants who sent messages of support to others they knew (Study 2, N = 120 students) or who expressed support to a new acquaintance in perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 41 publications
0
26
0
1
Order By: Relevance
“…Although expressers expected that gratitude recipients would feel positive, recipients reported feeling even more positive than the expressers anticipated. Later extensions of this research found similar effects for expressing simple compliments to others (Boothby & Bohns, 2021; Zhao & Epley, 2021a, 2021b), as well as for expressing support to someone in need (Dungan et al, in press).…”
Section: Prosociality and Well-beingmentioning
confidence: 63%
See 1 more Smart Citation
“…Although expressers expected that gratitude recipients would feel positive, recipients reported feeling even more positive than the expressers anticipated. Later extensions of this research found similar effects for expressing simple compliments to others (Boothby & Bohns, 2021; Zhao & Epley, 2021a, 2021b), as well as for expressing support to someone in need (Dungan et al, in press).…”
Section: Prosociality and Well-beingmentioning
confidence: 63%
“…In particular, gratitude and compliments are prosocial expressions uniquely tailored to enhance the recipient’s self-image typically by highlighting some positive attribute, which may create an especially positive experience for recipients (Zhao & Epley, 2021a). Expressions of support (Dungan et al, in press) come in cases when a recipient is in particular need, and hence may be uniquely appreciated in that moment. Random acts of kindness, in contrast, include a broader class of prosocial acts specifically intended to make another person feel positive, but not necessarily in ways that are uniquely tailored to a recipient’s self-image or delivered in a specific time of need.…”
Section: Prosociality and Well-beingmentioning
confidence: 99%
“…In addition to these, Silver and Small (2023) also suggest that actors may consider whether their behavior could convey negative signals to others, such as lacking competence. We agree wholeheartedly with this possibility, and document how misplaced concerns about competency can create barriers to expressing gratitude, sharing compliments, and providing social support (Dungan et al, 2022;Kumar & Epley, 2018;Zhao & Epley, 2021a; see also Boothby et al, 2018;Boothby & Bohns, 2021). Not only are actors likely to be thinking more about their own competency than recipients are (who are more likely to be attending to signals of another person's warmth; Abele & Wojciszke, 2007;Fiske et al, 2007;Wojciszke, 1994), they are also likely to think they are being evaluated less positively in terms of their competency than they actually are (Boothby et al, 2018;Dungan et al, 2022;Kumar & Epley, 2018).…”
Section: M Pr E S Sions: Com M U N Icat Ion a S A C U R E?mentioning
confidence: 65%
“…And yet, people may also at times be reluctant to reach out and express support out of the same concerns that might hold people back from expressing gratitude or giving compliments. Consistent with this possibility, participants who expressed support to others both online and in‐person expected recipients to feel less positive about their attempt to provide social support than the recipients actually did (Dungan et al, 2022). This tendency to underestimate how much recipients would appreciate social support was especially strong when people reached out to more distant others, such that those who were providing support expected more distant others to respond less positively than close others would, while actual recipients felt very positive regardless of how close they were to the person expressing their support.…”
Section: Undervaluing Kind Wordsmentioning
confidence: 95%
“…For instance, several experiments find that people have more positive expectations about their interactions with friends than with strangers, consistent with people learning from prior interactions, even though people's reported experiences were equally positive in interactions with friends versus strangers. These patterns have emerged when expressing social support (Dungan et al, 2022), disclosing secrets (Kardas et al, 2022b), and having conversations (Atir et al, 2022; Dunn et al, 2007; Kardas et al, 2022a; see also Experiments 4a–4b in Epley & Schroeder, 2014 for a related result). In some experimental designs, expectations before an interaction are compared against the same person's experience after the interaction rather than with another person's experience, a design that presumably holds social desirability constant before versus after an interaction but enables honest reports of learning from experience in the actual interaction.…”
Section: Why Is Sociality Undervalued?mentioning
confidence: 98%